The Effect of Transformational Leadership on Employees' Attitude by Considering the Mediating Role of Psychological Empowerment (Case Study: Municipality of Karaj, Region 1) - Mahsa Panahbehagh; Mehrdad Hosseini Shakib (Ital Publication, 2017)
This research was conducted to investigate the relation between transformational leadership and staff's attitudes with consideration of the mediating role in psychological empowerment. The purpose was applied type and the method used in this research was descriptive-survey. To collect the relevant data in this study, Sung's staff attitude standard questionnaire (2006), Bass & Alluvium's Transformational Leadership Questionnaire (2000) and Spreitzer's Psychological Capital Questionnaire (1998) were used. The reliability of each questionnaire was 0.786.0.802 and 0.799, respectively. The population studied was the staff and managers of the municipality in Region 1, Karaj with 280 persons. Regarding to their limited number, 162 individuals were selected randomly to determine the sample size using the Morgan table and the questionnaire was distributed among these individuals. To collect the information and data required to evaluate the research's hypotheses, a questionnaire and statistical analysis software as SPSS and LISREL were evaluated. At the inferential level, inferential techniques such as Kolmogorov-Smirnov's normal test, Pearson correlation test, and structural equation modeling were used to test the hypotheses. Based on the results, the studied hypotheses were accepted.